Quality of Working Life of Personnel at the Armed Forces Academies Preparatory School - Malitong, Suttipun; Piriyawattana, Wanlop (Journal of Roi Et Rajabhat University, 2025)
This research was a quantitative study with the objectives to: 1) study the quality of working life of personnel at the Armed Forces Academies Preparatory School, and 2) examine the factors affecting the quality of working life of personnel at the Armed Forces Academies Preparatory School. The research instrument was a questionnaire with a reliability coefficient of 0.938. The population consisted of 874 personnel, and the sample size of 274 was calculated using Taro Yamane’s formula. Stratified random sampling was employed, with stratification based on gender, age, education, marital status, position, rank, income, and years of employment. The statistics used for data analysis included frequency, percentage, mean, standard deviation, t-test, and one-way analysis of variance (ANOVA). The research findings revealed that the respondents’ opinions regarding the nature of work and the quality of working life were at a high level overall. When considered by aspect, the highest level was found in job satisfaction, followed by work environment, while the lowest was in compensation and welfare. The results of the hypothesis testing showed that personnel with different ages and positions had statistically significant differences in their overall quality of working life at the 0.05 level.